Meta-Cognition: A Theoretical Overview - Varghese, Mary (International Journal of Advance Research in Education & Literature (ISSN 2208-2441), 2019)
The recent developments in the field of education demands better pedagogical approaches and classroom practices. In recent years the concept of metacognition has emerged as a major focus of research interest in cognitive psychology. There has been a growing recognition that metacognition or self-awareness ‘including awareness of ourselves as learners, helps us to learn more effectively’. Metacognition refers to higher order thinking which involves active control over the cognitive processes engaged in learning. Activities such as planning how to approach a given learning task, monitoring comprehension and evaluating progress towards the completion of a task are metacognitive in nature. Because metacognition plays a critical role in successful learning, it is important to study metacognitive activity and development to determine how students can be taught to better apply their cognitive resources through metacognitive control. The article throws light on some of the important metacognitive strategies also.